Methodology of Use of Pedagogical Technologies in Music Lessons of General Education Schools - Khodjaev Khushnudbek Abidinovich (Journal of Learning on History and Social Sciences, 2024)
Before the lesson, the teacher tells the students which song to sing, and after which song, the lessons are organized based on a specific system, following the order. In such lessons, the teacher will have the opportunity to evaluate almost all students. The article describes the method of using pedagogical technologies in music classes of secondary schools.